Evaluation of exercise tolerance patients in cardiac rehabilitation D model based on 6 Minute Walk Test - Bielawa Lukasz; Prusik Katarzyna; Ossowski Zbigniew; Kortas Jakub; Wiech Monika; Prusik Krzysztof (Kharkov National Pedagogical University, 2012)
Evaluation of the results of 6-minute walk test depending on gender, age, left ventricular ejection fraction, the primary disease and BMI. Patients underwent assessment of Cardiac Rehabilitation Department in Szymbark in 2012 (80 people). Duration of rehabilitation for all patients was 21 days. The test was performed at the beginning and end of the cycle. Following the 3-week cardiac rehabilitation in the model D in a group of 80 patients with a mean age of 72 years achieved a statistically significant improvement in exercise capacity, expressed in the increase in test 6MWT distance by an average of 52 meters. In the study, men received final results statistically superior to women. The largest increase in the distance gained to patients after aortic valve prosthesis. People who are obese with a body mass index BMI over 30 have an average trip distance underperform both at baseline, final, and in the resulting increase of the distance than those with a BMI under 30. Prevention of obesity, one of the modifiable risk factors for cardiovascular disease should be the goal of training during cardiac rehabilitation patient education.